2010
DOI: 10.1155/2010/790431
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes as an Important Source of Serum S100B and Possible Roles of This Protein in Adipose Tissue

Abstract: Adipocytes contain high levels of S100B and in vitro assays indicate a modulated secretion of this protein by hormones that regulate lipolysis, such as glucagon, adrenaline, and insulin. A connection between lipolysis and S100B release has been proposed but definitive evidence is lacking. Although the biological significance of extracellular S100B from adipose tissue is still unclear, it is likely that this tissue might be an important source of serum S100B in situations related, or not, to brain damage. Curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 76 publications
4
49
0
1
Order By: Relevance
“…However, we demonstrated that a non-impact exercise (swimming) also increased serum S100B levels in humans, providing the basis to assume that extra-cerebral sources could additionally release/leak protein into blood (Dietrich et al 2003). For instance, experimental data show that under stress conditions, cardiomyocytes and adipocytes can leak S100B into medium (Mazzini et al 2005(Mazzini et al , 2009Gonçalves et al 2010). Furthermore, S100B protein is strategically located on the skeletal muscle membranes, sarcoplasmic reticulum, and transverse tubules acting in association with other proteins linked with calcium homeostasis (Arcuri et al 2002).…”
Section: Introductionmentioning
confidence: 80%
“…However, we demonstrated that a non-impact exercise (swimming) also increased serum S100B levels in humans, providing the basis to assume that extra-cerebral sources could additionally release/leak protein into blood (Dietrich et al 2003). For instance, experimental data show that under stress conditions, cardiomyocytes and adipocytes can leak S100B into medium (Mazzini et al 2005(Mazzini et al , 2009Gonçalves et al 2010). Furthermore, S100B protein is strategically located on the skeletal muscle membranes, sarcoplasmic reticulum, and transverse tubules acting in association with other proteins linked with calcium homeostasis (Arcuri et al 2002).…”
Section: Introductionmentioning
confidence: 80%
“…S100B increments have been reported in many conditions of brain injury and neurodegenerative diseases (Kleindienst et al, 2007;Rothermundt et al, 2003). Serum S100B protein comes from the brain and from other non-neural sources, particularly adipose tissue (Goncalves et al, 2010. In fact, serum S100B levels in humans appear to closely reflect adipose tissue mass (Gross et al, 2010;Steiner et al, 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…However, when BM-hMSCs were preincubated with ATP and then differentiated to the adipogenic lineage (ATP pretreat adipo), some master genes involved in adipogenesis such as ADIPOQ, a PPARg [52] and CEPBPA [53] target gene, and several adipocyte differentiation markers such as ESM1 [54] and S100B [55] were significantly increased compared to untreated counterpart (untr adipo). Moreover, ID1, a key transcription factor in osteogenic differentiation, was downregulated, as previously reported [56] (Fig.…”
Section: Gene Expression Profile Of Atp-treated Undifferentiated Bm-hmentioning
confidence: 99%